1984
DOI: 10.1113/expphysiol.1984.sp002867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limb Ischaemia on Blood Pressure and the Blood Pressure‐heart Rate Reflex in the Rat

Abstract: SUMMARYThe effects of bilateral hind-limb ischaemia on blood pressure and on the blood pressure-heart rate reflex have been studied in the rat. Limb ischaemia increased blood pressure and decreased the elevation and slope of the regression line describing the relationship between heart period (H.P.) and mean arterial pressure (M.A.P.). Nociceptive afferents from muscle receptors using long fibre tracts in the anterolateral part of the spinal cord seem to be responsible for the changes seen. The changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…When our results are considered in the light of other work on the effect of trauma on thermoregulation (Stoner, 1981) and cardiovascular homoeostatis (Little et al 1984a;Redfern et al 1984) it seems likely that they reflect changes in control mechanisms within the central nervous system. Three features of injury might be involved: loss of fluid from the circulation into the damaged tissue, the production of endogenous pyrogens and nociceptive afferent impulses.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…When our results are considered in the light of other work on the effect of trauma on thermoregulation (Stoner, 1981) and cardiovascular homoeostatis (Little et al 1984a;Redfern et al 1984) it seems likely that they reflect changes in control mechanisms within the central nervous system. Three features of injury might be involved: loss of fluid from the circulation into the damaged tissue, the production of endogenous pyrogens and nociceptive afferent impulses.…”
Section: Discussionmentioning
confidence: 80%
“…From the work of Cabanac & Massonnet (1974) on fever it would seem that their predominant effect is upon the set-point with little effect on the gain of the response. Our previous work Little et al 1984a;Redfern et al 1984) has suggested that the effect of trauma on thermal and cardiovascular homoeostasis is produced by nociceptive impulses ascending from muscle receptors in C-and A&-fibres to the deeper laminae of the dorsal horns of the spinal cord. From there long neurones cross to ascend in the opposite spinothalamic tracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, peripheral musculoskeletal injury leads to a reduction in baroreflex sensitivity in man (Little & Stoner, 1983;Anderson, Little & Irving, 1990), while bilateral hindlimb ischaemia (used as a model of injury) leads to a simultaneous increase in heart rate and blood pressure and a reduction in the sensitivity of the baroreflex in the conscious (Redfern, Little, Stoner & Marshall, 1984) and anaesthetized (Jones, Kirkman & Little, 1990;Turnbull, Kirkman, Rothwell & Little, 1992) rat. The afferent pathway from the injured tissue is at least partly neural (Redfern et al 1984), thus electrical stimulation of somatic afferent fibres has been used as a model of 'injury' in a number of studies (e.g. Overman & Wang, 1947;Rady, Little, Edwards, Kirkman & Faithful, 1991;Rady, Kirkman, Cranley & Little, 1992).…”
Section: Introductionmentioning
confidence: 99%